Hydrogen Sulfide Regulates Irisin and Glucose Metabolism in Myotubes and Muscle of HFD-Fed Diabetic Mice - Rajesh Parsanathan; Sushil K. Jain (MDPI AG, 2022)
Irisin, a novel myokine, is secreted by the muscle following proteolytic cleavage of fibronectin type III domain containing 5 (FNDC5) and is considered a novel regulator of glucose homeostasis. Cystathionine γ-lyase (CSE) produces hydrogen sulfide (H2S) and is involved in glucose homeostasis. We examined the hypothesis that H2S deficiency leads to decreased FNDC5 and irisin secretion, and thereby alters glucose metabolism. High-fat diet-fed mice exhibited elevated blood glucose and significantly reduced levels of CSE, H2S, and PGC-1α, with decreased FNDC5/irisin levels and increased oxidative stress in the muscle compared with those of normal diet-fed mice (control). High glucose or palmitate decreases CSE/PGC-1α/FNDC5 levels and glucose uptake in myotubes. Inhibitors (propargylglycine and aminooxyacetate) of H2S producing enzymes or CSE siRNA significantly decreased levels of H2S and FNDC5 along with PGC-1α; similar H2S-deficient conditions also resulted in decreased GLUT4 and glucose uptake. The levels of H2S, PGC-1α, and FNDC5 and glucose uptake were significantly upregulated after treatment with l-cysteine or an H2S donor. Myoblast differentiation showed upregulation of PGC-1α and FNDC5, which was consistent with the increased expression of CSE/H2S. These findings suggest that the upregulation of H2S levels can have beneficial effects on glucose homeostasis via activation of the PGC-1α/FNDC5/irisin signaling pathway.